Acetylcholinesterase Inhibitor Ameliorates Early Cardiometabolic Disorders in Fructose-Overloaded Rat Offspring - Victor Hugo Martins de Miranda; Camila Paixão Dos Santos; Pietra Petrica Neves; Antonio Viana Nascimento-Filho; Marina Rascio Henriques Dutra; Nathalia Bernardes; Maria Claúdia Irigoyen; Kátia De Angelis (MDPI AG, 2024)
Background: We investigate the role of galantamine on autonomic dysfunction associated with early cardiometabolic dysfunction in the offspring of fructose-overloaded rats. Methods: Wistar rats received fructose diluted in drinking water (10%) or water for 60 days prior to mating. Fructose overload was maintained until the end of lactation. The offspring (21 days after birth) of control and fructose-overloaded animals were divided into three groups: control (C), fructose (F) and fructose + galantamine (GAL). GAL (5 mg/kg) was administered orally until the offspring were 51 days old. Metabolic, hemodynamic and cardiovascular autonomic modulation were evaluated. Results: The F group showed decreased insulin tolerance (KITT) compared to the C and GAL groups. The F group, in comparison to the C group, had increased arterial blood pressure, heart rate and sympathovagal balance (LF/HF ratio) and a low-frequency band of systolic arterial pressure (LF-SAP). The GAL group, in comparison to the F group, showed increased vagally mediated RMSSD index, a high-frequency band (HF-PI) and decreased LF/HF ratio and variance in SAP (VAR-SAP) and LF-SAP. Correlations were found between HF-PI and KITT (r = 0.60), heart rate (r = −0.65) and MAP (r = −0.71). Conclusions: GAL treatment significantly improved cardiovascular autonomic modulation, which was associated with the amelioration of cardiometabolic dysfunction in offspring of parents exposed to chronic fructose consumption.